PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PENGURANGAN PADA SISWA KELAS 1 MELALUI MEDIA VISUAL JARIMATIKA DI UPT SD NEGERI SUMURGUNG 1 TUBAN - Arisa Nurfaidah; Wendri Wiratsiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted because the use of learning media by teachers has not been varied enough in teaching and learning activities. This scientific study aims to optimise mathematics learning achievement on subtraction material for grade 1 students at UPT SD Negeri Sumurgung 1 Tuban through the use of visual jarimatika media. The scope of this study covers the improvement of understanding of the concept of subtraction and the effectiveness of jarimatika media in helping students solve subtraction problems more easily and quickly. The subjects studied were students of grade 1 UPT SD Negeri Sumurgung 1 Tuban with a total of 12 people. The method applied in the research was classroom action research (PTK) using a cyclical model consisting of planning, implementation, observation, and reflection. Data was obtained through learning outcome tests. The research shows that the use of visual media jarimatika in subtraction material in grade 1 can significantly optimise student learning achievement. This can be observed based on the achievement of student completeness in the first cycle and the second cycle. The average student score in the first cycle was 65, then the average student score in the second cycle reached 77.5. Based on this, the use of jarimatika visual media in grade 1 subtraction material can be used as a solution to improve student learning performance.